Exploring the Power of Poetry for Fostering Critical Reflection: Adult Poetry Readers and Self-Reflexivity - Joellen E. Coryell; Robin Redmon Wright (Adult Education Research Conference, 2010)
This paper summarizes the results of a study of 22 self-identified poetry readers. The project was designed to discover the reasons why adults read poetry, how the love of poetry was inspired, and what they learn from poetry. Through qualitative data analyses, findings indicate that through multiple reading strategies and reflective personal engagement with the prose, our participants construct changed and enhanced personal meaning in their lives. Implications on how poetry and embodied, emotional, and spiritual knowing can be effective learning resources for critical adult educators are provided.